Synchronous endometrioid endometrial and ovarian carcinomas are biologically related: A clinico-pathological and molecular (next generation sequencing) study of 22 cases - Hájková, Nikola; Tichá, Ivana; Hojný, Jan; Němejcová, Kristýna; Bártů, Michaela; Michálková, Romana; Zikán, Michal; Cibula, David; Laco, Jan; Geryk, Tomáš; Méhes, Gábor; Dundr, Pavel (Oncology letters, 2019)
The criteria for distinction between independent primary tumors and metastasis from one site to the other in synchronous endometrioid endometrial and ovarian carcinoma (SEO) has been a matter of dispute for a long time. In our study we performed a comprehensive clinico-pathological and molecular analysis of 22 cases of SEO. Based on conventional clinico-pathological criteria the cases were classified as independent primary tumors (10 cases) and metastasis from one location to the other (12 cases). All tumors were analyzed by NGS with a panel of 73 genes (219 kbp). Clonal origin was confirmed in all cases by at least one shared mutation in PTEN, AKT1, PIK3CA, KRAS, TP53 and ARID1A. Two patients carried germline pathogenic mutation in cancer-predisposing genes BRCA1 or BARD1. Microsatellite instable phenotype was detected in 5/22 (22.7%) SEO, but in one case only in the endometrial tumor. In conclusion, our results showed that all 22 SEOs were clonally related, irrespectively of their clinico-pathological features. Even low grade and low stage tumors classified as independent primaries, according to the conventional morphological criteria, have a clonal origin. From the practical point of view, only the conventional morphological criteria should be used for the classification (staging) of these tumors. However, molecular profiling of these tumors may have prognostic and predictive meaning.
Keywords: endometrial carcinoma; ovarian carcinoma; synchronous tumors; NGS; endometrioid carcinoma